Influence of soda lime glass addition on the dielectric properties of CCTO ceramics - Ab Rahman, M.F; Rejab, N.A; Ahmad, Z.A; Mohamed, J.J; Ain, M.F; Abdullah, S. (2018)
The dielectric properties of CCTO ceramics with soda-lime glass addition was investigated. The addition of soda lime glass was varied from 0 - 0.05 wt.% by solid-state reaction. Both XRD patterns of CCTO and CCTO-glass sintered samples showed the formation of CCTO phase with minor peaks of CuO phase, respectively. The phase area analysis of CCTO and CCTOglass proved that the CCTO phase was found to be decreased while the grain boundaries area of CuO + glass was then increased after the addition of soda-lime glass. The dielectric properties of corresponding samples indicated that both εr and tan δ were reduced with glass addition. Thus, it shows that the soda lime glass addition has a significant effect on dielectric properties of CCTO ceramics.